Review of the Boran in Kenya - Kimenye, D. (1983)
Reports on the improved Boran in Kenya. Discussions and data on history of breeding, breed description, and distribution, birth weight, weaning age and weight, milk and fat production, age at first calving, calving percentage and interval, post weaning weights, adaptability and disease resistance included.